PENGARUH PIJAT ENDORPHIN TERHADAP INTENSITAS NYERI KALA I PERSALINAN (Politeknik Kesehatan Kemenkes Bandung, 2022)
The process of childbirth is identical to the pain that will be endured. Labor pain is caused by the contraction of the uterus in an attempt to give birth. Coping with labor pain is by means of pharmacological and non-pharmacological therapy. One way of non-pharmacological management to reduce labor pain is with Endorphin Massage. This EBCR aims to determine the effect of Endorphin Massage on the intensity of pain in the first stage of labor. The method used is literature review with experimental design research design. Search sources use 2 databases, namely: Google Scholar and Portal Garuda with the year 2016-2021 published. Giving Endorphin Massage for 5-15 minutes and it is proven that the mother feels more relaxed and the pain is reduced because when given endorphin massage therapy physiologically the mother's body will stimulate the release of endogenous analgesics (endorphins), so that it can inhibit pain transmission by increasing the circulation of neurotransmitters and lowering the system. sympathetic nerves so that there is a decrease in muscle tension, a decrease in anxiety and pain will decrease. Conclusion Endorphin Massage is an effective way to reduce pain in the first stage of labor.